To multiply this expression out, you can use the FOIL method:
- First: Multiply the First terms of each set of parentheses: (-3y) * (y) = -3y^2
- Outer: Multiply the Outer terms of each set of parentheses: (-3y) * (3) = -9y
- Inner: Multiply the Inner terms of each set of parentheses: (2) * (y) = 2y
- Last: Multiply the Last terms of each set of parentheses: (2) * (3) = 6
Now, add the resulting terms together:
- -3y^2 - 9y + 2y + 6
Simplifying this expression by combining like terms, we get:
- -3y^2 - 7y + 6
Therefore,
(-3y+2)(y+3) = -3y^2 - 7y + 6
simplify and show me how
(-3y+2)(y+3)
1 answer